Religion and Reductionism, Essays on Eliade, Segal, and the Challenge of the Social Sciences for the Study of Religion. - Idinopulos; Yonan (Editors) (Numen Book Series, 1993)
This volume on Religion and Reductionism grew out of a conference convened in November, 1990, where the participants were asked to respond to the conceptual and methodological problem of reductionism in the academic study of religion. The conference focused on the writings of Robert A. Segal and his defence of reductionism and criticism of Mircea Eliade's non-reductive interpretation of religion. At the Miami conference some of the most important and enduring questions were raised: (1) What is religion? (2) What is religion and/or religious meaning? (3) How should religion be studied and taught? (4) What are the possibilities and limits of social scientific analyses of religious phenomena? (5) What is reductionism? (6) What is anti-reductionism? These and other questions on religion and reductionism are widespread and invite serious consideration; they help to illuminate the basic issues that are at the core of any study of the world's major religions.